Towards Trustworthy and Fresh Data Delivery in 6G IoT: A DRL-aided Cognitive NOMA and Backscatter Framework - Mazhar, Neha; Ullah, Syed Asad; Basheer, Shakila; Jung, Haejoon; Solaija, Muhammad Sohaib J.; Mahmood, Aamir; Gidlund, Mikael (Institute of Electrical and Electronics Engineers Inc., 2025)
The proliferation of large-scale Internet-of-things (IoT) deployments and the emergence of 6G wireless technologies have created a pressing need for intelligent, energy-aware, and low-latency communication frameworks. In this work, we propose a novel two-phase reinforcement learning (RL)-based architecture designed to minimize the age of information (AoI) in 6G-enabled IoT networks. Our approach integrates (i) a deep deterministic policy gradient (DDPG)-driven backscatter-assisted cognitive radio non-orthogonal multiple access (CR-NOMA) scheme in the uplink, and (ii) a lightweight Q-learning-based power-domain NOMA (PD-NOMA) strategy for the downlink. In the uplink, energy harvesting (EH) sensors employ deep RL to jointly optimize backscatter reflection coefficients and transmission scheduling over shared spectrum using CR-NOMA. This enables energy-efficient communication and reduced AoI under dynamic energy and channel conditions. In the downlink, the edge node serves multiple IoT users simultaneously using PD-NOMA, where a Q-learning agent intelligently decides whether to transmit fresh or cached data to each user based on battery levels, channel quality, and information freshness. Both phases are modeled as Markov decision processes (MDPs), allowing agents to learn independently and converge toward optimal policies that balance information freshness, spectral efficiency (SE), and energy constraints. Extensive simulations demonstrate that the proposed framework effectively reduces AoI across both phases, with consistent convergence even under varying sensor densities and EH conditions. Moreover, by relying on explainable and verifiable learning mechanisms, our model addresses emerging concerns around reliability and trustworthiness in artificial intelligence (AI)-driven 6G-IoT systems. This framework represents a step toward scalable, adaptive, and responsible AI integration for future mission-critical IoT applications. © 2025 Elsevier B.V., All rights reserved.
Keywords: age of information (AoI); cognitive radio non-orthogonal multiple access (CR-NOMA); deep deterministic policy gradient (DDPG); Internet-of-things (IoT); Markov decision processes (MDPs); power-domain NOMA (PD-NOMA); reinforcement learning (RL); spectral efficiency (SE) and artificial intelligence (AI)